Computationally efficient thermal network model and its application in optimization of battery thermal management system with phase change materials and long-term performance assessment. (1st February 2020) - Ling, Ziye; Lin, Wenzhu; Zhang, Zhengguo; Fang, Xiaoming
Highlights: Develop an efficient thermal network model for PCM thermal management systems. The model has a high accuracy, high computation efficiency and high resolution. The model optimizes the PCM properties for low temperature thermal management. The model analyzes the long-term impacts of temperature field on battery life. Abstract: This paper presents a simple 2D thermal network model for a battery thermal management system with phase change materials (PCMs). An equivalent electric circuit model is developed to solve heat transfer problems that include the processes of battery heat generation and PCM thermal storage. This thermal network model is compact and accurate. The simulation time is saved by 99% compared with a conventional numerical model, whereas the average prediction error of battery temperature is lower than 1 °C. This model is applied for the rapid optimization of the PCM properties to warm up a battery pack rapidly during cold starts. The results demonstrate that the PCM suitable for thermal management under low temperatures should have a melting point of approximately 40 °C, high thermal conductivity of over 5.4 W/m K, and a low latent heat storage density of less than 0.0145 kJ/m 3 . Utilizing its high computation efficiency and resolution for capturing the temperature distribution in 2D, the model can quantitatively assess the long-term effect of the thermal management system on the life of a battery module during a 10, 000-hour charge–discharge cycle. A lifespan model that integrates a battery capacity fade model into the thermal network is developed and the simulation results verify that a lower temperature and temperature difference reduce the capacity loss in a multi-cell module. The thermal network model is efficient to design and optimize the thermal management system for a real-size battery pack, based on the assessment of its long-term impacts on battery performance.